(CA/GT)(n) microsatellites affect homologous recombination during yeast meiosis - Gendrel, Christiane-Gabrielle (Cold Spring Harbor Laboratory Press, 2000)
One of the most common microsatellites in eukaryotes consists of tandem arrays of the dinucleotide GT. Although the study of the instability of such repetitive DNA has been extremely fruitful over the last decade, no biological function has been demonstrated for these sequences. We investigated the genetic behavior of a region of the yeast Saccharomyces cerevisiae genome containing a 39-CA/GT dinucleotide repeat sequence. When the microsatellite sequence was present at the ARG4 locus on homologous chromosomes, diploid cells undergoing meiosis generated an excess of tetrads containing a conversion of the region restricted to the region of the microsatellite close to the recombination-initiation double-strand break. Moreover, whereas the repetitive sequence had no effect on the frequency of single crossover, its presence strongly stimulated the formation of multiple crossovers. The combined data strongly suggest that numerous recombination events are restricted to the initiation side of the microsatellite as though progression of the strand exchange initiated at the ARG4 promoter locus was impaired by the repetitive sequence. This observation corroborates in vitro experiments that demonstrated that RecA-promoted strand exchange is inhibited by CA/GT dinucleotide tracts. Surprisingly, meiotic instability of the microsatellite was very high (>0.1 alterations per tetrad) in all the spores with parental and recombinant chromosomes.